Effect of ultrasonic-assisted extraction (UAE) method extraction time on the cytotoxic activity of young bay leaf extract (Eugenia polyantha Wight) on T47D breast cancer cells and determination of flavonoid levels - Sufa , Riisyda Faila; Hidayati, Devi Nisa (Universitas Ahmad Dahlan, 2025)
The most common type of cancer in Indonesia is breast cancer. Anticancer medications made of natural ingredients are beginning to be produced. Methanol extract of young bay leaves (Eugenia polyantha) has anticancer activity at moderate levels. The compounds that function as anticancer are flavonoids. The duration and extraction technique can have an impact on how active chemicals are extracted from natural materials. Through variations in the duration of the extraction process for young bay leaves, this study seeks to ascertain the amounts of flavonoids and the cytotoxic activity of T47D breast cancer.Young bay leaf ethanol extract (EEDSM) was obtained using the Ultrasonic assisted extraction (UAE) method with 70% ethanol solvent and varying extraction times of 5, 15, and 25 minutes. EEDSM total flavonoid content was tested using the UV-visible spectrophotometric method with quercetin as a comparison. The cytotoxic test of the ethanol extract of young bay leaves was carried out using the MTT assay method. Determining the IC50 value uses linear regression and probit analysis. It will also use One Way ANOVA to quantitatively determine the significance of the difference between the effect of extraction time and the IC50 value on T47D breast cancer cells. The results showed that EEDSM with extraction times of 5, 15, and 25 minutes had total flavonoid levels of 2.13mgQE/g, 2.36mgQE/g, and 2.61mgQE/g and cytotoxic activity with an IC50 value of 843μg/mL; 1007μg/mL; and 735μg/mL. EEDSM 5 and 25 minutes were shown to have moderate levels of cytotoxic activity.